THE EFFECT OF COMMUNICATIVE ACTIVITIES ON THE SPEAKING ABILITY OF 8th GRADE STUDENTS OF SMP N 23 PEKANBARU - Yunita, Bela; ', Marzuki; ', Novitri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract:This was an experimental research. This research was about the effect of communicative activitieson the students speaking ability. The objective was to see the effect of communicative activities on the speaking ability of the 8th grade students of SMP N 23 Pekanbaru. It was conducted to the 8th grade students of SMP N 23 Pekanbaru especially VIII G as the subject of research. There are two communicative activities applied, they are information gap and scramble sentence. Speaking testas used as the tools of collecting the data. Pre-test are conducted to know students speaking ability before the treatment and post-test to know the students’ speaking ability after the treatment. They need to retell a fable. The data was analyzed by using SPSS. The result of this research showed that communicative activitieshave significant effect and positive impactto the students’ speaking ability. It indicates the improving of students speaking abilityaspects in the result of pre-test and post-test.Key Words: Communicative activities, speaking ability, information gap, scramble sentence, fable